2017
DOI: 10.1002/anie.201700231
|View full text |Cite
|
Sign up to set email alerts
|

Auto‐Tandem Catalysis with Frustrated Lewis Pairs for Reductive Etherification of Aldehydes and Ketones

Abstract: Herein we report that a single frustrated Lewis pair (FLP) catalyst can promote the reductive etherification of aldehydes and ketones. The reaction does not require an exogenous acid catalyst, but the combined action of FLP on H , R-OH or H O generates the required Brønsted acid in a reversible, "turn on" manner. The method is not only a complementary metal-free reductive etherification, but also a niche procedure for ethers that would be either synthetically inconvenient or even intractable to access by alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 62 publications
(14 reference statements)
0
38
0
Order By: Relevance
“…[12] Subsequents tudies revealed that the borane I itself was incapable of promoting the 1,3-allylic shift because of the confined space around the Lewis acidic center. However, as our observations [13] suggest,t he allylic transposition (Scheme 2) could proceed by means of either aL ewis acid induced Lewis acid promotion (hydride abstraction from HSiEt 3 with borane I) [16] or hidden proton catalysis [17] (protonationb yt race amount of borane I-watera dduct [11,18] ). Finally,i tw as established that the enhanced steric hindrance around the borane I was ac ritical factor in this reductiveI reland-Claisen reaction.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…[12] Subsequents tudies revealed that the borane I itself was incapable of promoting the 1,3-allylic shift because of the confined space around the Lewis acidic center. However, as our observations [13] suggest,t he allylic transposition (Scheme 2) could proceed by means of either aL ewis acid induced Lewis acid promotion (hydride abstraction from HSiEt 3 with borane I) [16] or hidden proton catalysis [17] (protonationb yt race amount of borane I-watera dduct [11,18] ). Finally,i tw as established that the enhanced steric hindrance around the borane I was ac ritical factor in this reductiveI reland-Claisen reaction.…”
mentioning
confidence: 84%
“…However,t he adaptation of borane-promoted hydrosilylation for reductiveI reland-Claisen rearrangement was far from being straightforwardbecause of the substrate inhibition and the extreme water sensitivity of the highly oxo-philic, hard-type boron catalyst. Nevertheless, based on our previousw ork in frustrated Lewis pair hydrogenation [11] and hydrosilylation, [12] we conceived that it is possible to tackle these anticipated constraints of ab orane-catalyzed reductive Ireland-Claisen rearrangement by employing structurally welldesigned, so-called size-exclusion boranes. The enhanced steric shieldinga roundthe boron Lewis acid centerserves to prevent or retard the complexation ability with Lewis basis (including water and carbonyls' oxygen), while retainingt he capacity of cleavage of the silanes and might drive the chemo-and regioselectivity of the hydrosilylation of acrylates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of substituted 3-benzoylamino-5-oxo-5,6,7,8tetrahydrocoumarins (427) from 1,3-cyclohexanediones (195,197), hippuric acid (407), and TEOF (5) (or other one-carbon synthetic equivalents, such as diethoxymethyl acetate or N,Ndimethylformamide dimethyl acetal) in acetic anhydride has been described (Scheme 122). 375 In 378 In 2016, estrone 3-secondary ethers (435) were made through the eco-friendly etherication/aromatization reaction of readily accessible dienone (432) with trialkyl orthoformates (127,433,434), as alkylating agent, in a 1 : 5 molar ratio by triic acid (TfOH, 0.5 mmol) in the corresponding alcohol (5 mL) at 100 C for 2 h in 80-87% yields (Scheme 125). The above-mentioned procedure was applied for the generation of three marketed 3-etheried estrogen drugs, quinestrol, quinestradol, and nilestriol, utilizing 19-hydroxyandrost-4-ene-3,17-dione as a commercially available precursor.…”
Section: Synthesis Of Coumarin Derivativesmentioning
confidence: 99%
“…However,this reactivity of FLPs eventually inhibits their isolation and makes them unstablef or shelf storage, which somewhat limits their utility in organic synthesis. [11] We therefore envisioned as trategy to control the interconversion between CLAs and FLPs by using externals timuli, which should offer an opportunity to use isolable and shelfstable CLAs as precursors for active FLPs under closely controlledr eactionc onditions rather than under ambientc onditions ( Figure 4c). [12] In order to achieve this "frustration revival strategy", we designed PoxIms that undergo significant changes to the spatiale nvironments urrounding their carbene centert hrough rotation of the N-phosphineo xide moiety.…”
Section: Strategic Use Of Poxims As External Stimuli-responsive Lewismentioning
confidence: 99%